2016
DOI: 10.18632/oncotarget.13197
|View full text |Cite
|
Sign up to set email alerts
|

Subsite-specific association of DEAD box RNA helicase DDX60 with the development and prognosis of oral squamous cell carcinoma

Abstract: The clinical significance and biological function of DEXD/H box helicase 60 (DDX60) in oral cancer remains unknown. Herein, we evaluated the association of DDX60 expression with tumorigenesis and the prognosis of oral squamous cell carcinoma (OSCC). DDX60 expression was examined by immunohistochemistry on tissue microarray slides of 494 OSCC patients, including 180 buccal mucosal SCC (BMSCC), 241 tongue SCC (TSCC), and 73 lip SCC (LSCC) patients. DDX60 expression was significantly increased in all three subsit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
2
28
1
Order By: Relevance
“…Although our focus here was LFNG, many of the other genes we discovered in our analysis may also regulate melanoma metastasis. For example, the DEXD/H box helicase 60 ( DDX60 ) gene, a known regulator of the antiviral response and a DNA‐/RNA‐binding protein, has been reported to be associated with the development and prognosis of squamous cell carcinoma (Fu et al ., ). Similarly, PTK2B has been reported to be involved in the CCR7‐mediated regulation of metastasis in squamous cell carcinoma (Yue et al ., ) and was found to be downregulated in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Although our focus here was LFNG, many of the other genes we discovered in our analysis may also regulate melanoma metastasis. For example, the DEXD/H box helicase 60 ( DDX60 ) gene, a known regulator of the antiviral response and a DNA‐/RNA‐binding protein, has been reported to be associated with the development and prognosis of squamous cell carcinoma (Fu et al ., ). Similarly, PTK2B has been reported to be involved in the CCR7‐mediated regulation of metastasis in squamous cell carcinoma (Yue et al ., ) and was found to be downregulated in our study.…”
Section: Discussionsupporting
confidence: 65%
“…However, studies have shown that AIM2 inhibits the occurrence of CRC by regulating intestinal epithelial cells via an inflammasome-independent manner [ [28]. Therefore, we hypothesize that DNA sensors may play important roles in the development of colitis and CRC.…”
Section: Introductionmentioning
confidence: 92%
“…In total, 428 tissues obtained from primary BMSCC (n = 179) and TSCC (n = 249) between 1993 and 2006 were embedded in paraffin to construct a TMA, as described previously [19] Each patient tissue contained 1 core of adjacent normal tissue and 2 cores of tumor tissue in the TMA block. The blocks were cut in 4 µm paraffin sections.…”
Section: Tissue Specimens and Tissue Microarray (Tma) Constructionmentioning
confidence: 99%